Optimization of Highly Sensitive Screen Printed Electrode Modified With Cerium (IV) Oxide Nanoparticles for Electrochemical Determination of Oxymetazoline Hydrochloride Using Response Surface Methodology. Issue 4 (12th February 2020) - Abdel-Raoof, Ahmed M.; Abdel-Monem, Ahmed H.; Almrasy, Ahmed A.; Mohamed, Tahany F.; Nasr, Zeinab A.; Mohamed, Ghada F.
Abstract : In the present work, a sensitive optimized electrochemical screen-printed electrode chemically modified with cerium nanoparticles was assigned for the determination of oxymetazoline hydrochloride. The sensing membrane was based on incorporation of ion paring agent i.e. tetraphenylborate associated with the drug as an electroactive material. Asides, paraffin oil was used as a pasting liquid for in this screen-printed electrode whereas cerium nanoparticles, commonly known as nanoceria, were used as oxide ion conductors to increase the electrode surface area and electrical conductivity. Optimization of the experimental parameters was performed using a response surface methodology which enables a graphical clarification of the linkage between different experimental factors and the slope response. The modified sensor with cerium nanoparticles displays a stable and significant linear response with a reproducible potential for five months at Nernstian slope of 59.07 ± 0.76 mV decade −1 over the concentration range (5 × 10 −6 −1 × 10 −2 mol.l −1 ) at 25 ± o C with a detection limit of 9.72 × 10 −7 mol l −1 . Furthermore, the proposed approach was successfully used for the analysis of the drug in its pure and dosage form.